Evaluation of Fetuses Diagnosed with Megacystis During Prenatal Period - Kemal Sarsmaz; Busra Kanyildiz; Gokcen Orgul; Gokhan Karakoc; Hasan Eroglu; Dilek Sahin; Aykan Yucel (Gynecology Obstetrics & Reproductive Medicine)
Objectives: Fetal megacystis is very rare; however this problem may be associated with other structural or chromosomal abnormalities leading to morbidity and mortality. Due to renal injury and pulmonary hypoplasia, prognosis is poor especially in fetuses with early onset oligohydramnios. In this study, we evaluated the management strategies and outcomes of fetal megacystis in our hospital.